Ecosystem services to support environmental and socially sustainable decision-making - Rusch, Veronica Elena; Rusch, Graciela Mónica; Goijman, Andrea Paula; Varela, Santiago Agustin; Claps, Leonardo (Asociación Argentina de Ecología, 2019)
The theory of ecosystem services (ES) needs to be operationalized to contribute to practices leading to sustainable use of ecosystems, which includes solving trade-offs between private and public benefits and incorporating monetary and non-monetary values to help inform decisions. We developed a framework to analyse the impacts of farmers’ management alternatives on Nothofagus antarctica (G. Forst.) Oerst. forest in northern Patagonia, and analysed synergies and trade-offs between private and public benefits based on three conceptual and methodological approaches: a) a state-and-transition model of ecosystem dynamics, and b) indicators of values of ecosystem service benefits based on the cascade model, implemented as c) a decision support tool based on a Bayesian network. We optimized a utility function for short (0-10 yr) and long (70-140 yr) term management decisions (levels of grazing, logging and tree planting) based on monetary and non-monetary indicators of benefits that fulfilled “farmer’s satisfaction” objectives. We then assessed the consequences of these decisions on the fulfilment of public benefits as defined by the National Forest Law when projected into short (0-10 yr), intermediate (10-40 yr) and long (70-140 yr) time horizons. We found that when short-term decisions are projected into a long-time horizon, they lead to high losses of benefits, mainly linked to “regulating and maintenance” ES. On the other hand, long-term decisions improved the level of benefits in degraded systems but resulted in the degradation of well-preserved forests. The decisions that optimize farmer’s satisfaction did not change with different weights of “farm income” in the utility function, indicating the absence of trade-offs between monetary and non-monetary benefits considered in the utility function. The tool developed helps to show long-term impacts of management, and discloses cause-effect relationships between levels of use and multiple benefits. It can therefore support measures aiming to raise awareness about degradation trends, and improve the functional understanding of the system wich can help to identify solutions for socio-economic and environmental sustainability.